Induction and Plant Regeneration of Callus in Dendrobium - Cossall, Cynthia Psyquay (2000)
The present study examines the effects of some selected chemicals and physical treatments on protocorm-like body (plbs) of orchid hybrid, Dendrobium Kasem White . This is an attempt at initiating embryogenic callus, and setting conditions optimal for its maintenance and regeneration into plbs and hence plantlets. This protocol was initiated to establish a system for the transfer of genetic material through genetic engineering technology. The study was conducted in four main parts, a set of preliminary studies, callus induction, maintenance and regeneration. The critical concentration of picloram and kinetin for the survival of wounded and unwounded plbs were obtained from the preliminary studies. Optimal concentration of picloram and kinetin for unwounded plbs ranged from 0 to 1.0 mg/l. For wounded plbs the concentration ranged from 0 to 0.5 mg/l and 0 to 1 mg/l for picloram and kinetin respectively. Callus-like tissue formation was observed from unwounded plbs cultured on % MS supplemented with 0.6 to 0.9mg/l picloram and 0.3 to 0.6 mg/l kinetin treatments. The best concentrations were 0.75 mg/l picloram and 0 .60 mg/l kinetin. Induction was achieved in the 40-day dark treatment. Wounded plbs produced callus-like tissue on 0.1 mg/l picloram + 0.8 mg/l kinetin and 0 mg/l picloram + 1.0 mg/l kinetin treatments after 30 days of culture in the dark. Callus-like tissue remained viable in both solid and liquid medium of % MS supplemented with 0.75 mg/l picloram and 0.6 mg/l kinetin, cultured in the dark. Through several modifications of medium, the callus-like tissue regenerated into plbs when the medium was devoid of hormones and cultured in the light. Regenerated plbs formed shoots and roots upon transfer to medium with lBA and BA.